On Codes over the Rings fq + ufq + vfq + uvfq - M Yaghi, Ibrahim; Ashker, Mohammed M Ali (GANIT: Journal of Bangladesh Mathematical Society, 2018)
In this paper, we study the structure of linear and self dual codes of an arbitrary length n overhearing Fq + uFq + vFq + uvFq, where q is a power of the prime p and u2 = v2 = 0, uv = vu, Also we obtain the structure of consta-cyclic codes of length n = q − 1 over the ring Fq + uFq + vFq + uvFq in the light of studying cyclic codes over Fq + uFq + vFq + uvFq in [6]. This study is a generalization and extension of the works in [7], [8], and [10]. GANIT J. Bangladesh Math. Soc.Vol. 38 (2018) 57-71